2008
DOI: 10.1093/rpd/ncn173
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of health hazards resulting from a radiological terrorist attack in a city

Abstract: In recent years, the concern for protection of urban populations against terror attacks involving radiological, biological or chemical substances has attracted increasing attention. It sets new demands to decision support and consequence assessment tools, where the focus has traditionally been on accidental exposure. The aim of the present study was to illustrate issues that need to be considered in evaluating the radiological consequences of a 'dirty bomb' explosion. This is done through a worked example of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 18 publications
0
28
0
Order By: Relevance
“…For instance, some plausible scenarios involving malicious dispersion of radionuclides would generate large particles that would be comparatively easy to remove from impermeable surfaces (Andersson et al, 2008b).…”
Section: Tablementioning
confidence: 99%
“…For instance, some plausible scenarios involving malicious dispersion of radionuclides would generate large particles that would be comparatively easy to remove from impermeable surfaces (Andersson et al, 2008b).…”
Section: Tablementioning
confidence: 99%
“…The threat of deliberate dispersal of radioactive materials in an urban environment has received considerable attention in the wake of the September 11 attacks in 2001 [1][2][3][4][5][6][7]. A radiological dispersal device (RDD) is one of many conceivable ways in which radioactive material could be maliciously dispersed and exposed to the general public [6].…”
Section: Introductionmentioning
confidence: 99%
“…Even if the direct health effects from radiation exposure will be minimal, the costs associated with the potential disruption and remediation will be considerable [10]. This provides strong motivation for developing accurate and detailed models to assist nuclear emergency stewards and first responders in properly assessing and planning emergency response strategies [2,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here consequence assessment models can be highly valuable. Simplified calculations have indicated that at least under some circumstances, a well-staged 'dirty bomb' attack could over several kilometres distance result in significant exposure from dispersed contaminants (Andersson et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%